Non-Common-Sensical: An Inference of Guilt to Sanction Non-Compliance - Slankard, Jesse (Victoria University of Wellington Law Review, 2011)
The Criminal Procedure (Reform and Modernisation) Bill is currently before the New Zealand Parliament. The Bill will implement mandatory defence disclosure of the issues in dispute at a pre-trial hearing stage. This paper addresses the enforcement mechanism adopted by the Bill – an inference of guilt from non-compliance – and examines the suitability of the inference as an enforcement mechanism. It outlines the compatibility of the inference with the existing framework of evidence law in New Zealand and suggests changes to the Bill that are necessary to ensure the inference is exercised in a consistent and justifiable way.